2022
DOI: 10.3390/su142416376
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Supply Chain Financial Credit Risk Based on PCA-GA-SVM Model

Abstract: Supply Chain Finance (SCF) is a new type of financing business carried out by commercial banks on the basis of supply chain management, which effectively promotes the healthy development of the supply chain. As the most typical mode of SCF, accounts receivable financing mode can use the part of accounts receivable occupying working capital for financing, which is widely used. In order to effectively manage the credit risk in the Supply Chain Finance and maintain the healthy operation of the supply chain, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Internationally, scholars tend to explore supply chain finance from the perspectives of corporate operations and finance, while in China, research focuses more on corporate management practices. Additionally, existing studies have concentrated on topics such as supply chain finance models, risk management, and green supply chain finance [9][10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internationally, scholars tend to explore supply chain finance from the perspectives of corporate operations and finance, while in China, research focuses more on corporate management practices. Additionally, existing studies have concentrated on topics such as supply chain finance models, risk management, and green supply chain finance [9][10][11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Combined [1] with a self -regulating mobile average model, index smooth model and RNN to form a hybrid model. The verification consequence indicate that the hybrid model is greater than simply using RNN; Li Haiyan [2] adopts the main component analysis method [2]. The method of combining PCA, genetic algorithms, and BPNN is used for the price prediction of the share marker, and the results prove that the preciseness of the prediction is more accurate; Y. J. BAEK [3] put forward a classical model named LSTM that prevents overfitting and the share market index prediction framework as the foundation of the LSTM model.…”
Section: Introductionmentioning
confidence: 97%
“…With the rapid development of technology and data, emerging models based on machine learning and artificial intelligence have emerged. Models such as support vector machine (SVM) (Harris, 2013), random forest (Wang, 2022a), deep learning (Zhang et al, 2020), and neural networks (Li & Fu, 2023;Wang, 2022b) have been shown to have higher predictive ability and flexibility in credit risk assessment. For example, Li & Fu (2023) proposed a credit risk prediction model based on PCA-GA-SVM for supply chain finance.…”
Section: Introductionmentioning
confidence: 99%
“…Models such as support vector machine (SVM) (Harris, 2013), random forest (Wang, 2022a), deep learning (Zhang et al, 2020), and neural networks (Li & Fu, 2023;Wang, 2022b) have been shown to have higher predictive ability and flexibility in credit risk assessment. For example, Li & Fu (2023) proposed a credit risk prediction model based on PCA-GA-SVM for supply chain finance. The running results show that the model has good genera-lization ability and can provide a reference for commercial banks to improve the credit risk management ability of Supply Chain Finance.…”
Section: Introductionmentioning
confidence: 99%